Using Structured and Unstructured Data to Refine Estimates of Military Sexual Trauma Status Among US Military Veterans - GUNDLAPALLI, Adi V. (Stud Health Technol Inform, 2017)
Sexual trauma survivors are reluctant to disclose such a history due to stigma. This is likely the case when estimating the prevalence of sexual trauma experienced in the military. The Veterans Health Administration has a program by which all former US military service members (Veterans) are screened for military sexual trauma (MST) using a questionnaire. Administrative data on MST screens and a change of status from an initial negative answer to positive and natural language processing (NLP) on electronic medical notes to extract concepts related to MST were used to refine initial estimates of MST among a random sample of 20,000 Veterans. The initial MST positive screen of 15.4% among women was revised upward to 21.8% using administrative data and further to 24.5% by adding NLP results. The overall estimate of MST status in women and men in this sample was revised from 8.1% to 13.1% using both data elements.